Developing a protocol for normothermic ex‐situ limb perfusion. Issue 2 (9th October 2017) - Duraes, Eliana F. R.; Madajka, Maria; Frautschi, Russell; Soliman, Basem; Cakmakoglu, Cagri; Barnett, Addison; Tadisina, Kashyap; Liu, Qiang; Grady, Patrick; Quintini, Cristiano; Okamoto, Toshihiro; Papay, Francis; et al.
Abstract : Background: Ischemia time represents a significant limitation for successful extremity transplantation because of the rapid deterioration of ischemic muscle. Normothermic ex‐situ preservation is an emergent method to prolong the organ viability following procurement, by replicating the physiologic conditions. The aim of this study was to develop an ex‐situ normothermic limb perfusion system to preserve the viability and function of porcine limbs for 12 hours following procurement. Methods: A total of 18 swine limbs were perfused. Thirteen limbs were used to develop the perfusion protocol. Five limbs were perfused according to the optimized protocol. These limbs were perfused at 39°C for twelve hours using an oxygenated colloid solution containing red blood cells. Glucose and electrolytes were kept within physiologic range by partial perfusate exchange. Limb specific perfusion quality was assessed by muscle contractility upon electrical nerve stimulation, compartment pressure, creatine kinase (CK) and myoglobin concentrations, tissue oxygen saturation (near infrared spectroscopy), indocyanine green angiography, and infrared radiation by thermographic imaging. Results: The last five limbs reached the 12 hours' perfusion target maintaining normal compartment pressure (16.4  ± 8.20 mmHg), minimal weight increase (0.54 ± 7.35%), and mean muscle temperature of 33.6 ± 1.67°C. Myoglobin and CK concentrations were 875 ± 291.4 ng/mL, and 53344 ± 14850.34 U/L, respectively, at the end of perfusion. Muscle contraction was present in all limbs until cessation of perfusion. Differences in uniformity and quality of distal perfusion were identified with thermography and angiography imaging at 12 hours of perfusion. Conclusions: Ex‐situ normothermic limb perfusion preserves swine limb physiology and function for at least 12 hours.